Bacterial cellulose active composite material as well as preparation method and application thereof

By combining bacterial cellulose with chitosan and cinnamon essential oil, and using emulsion coating and non-covalent bonding technology, the composite material prepared is solved, and the cost and complex operation of existing bacterial cellulose in food packaging is achieved, achieving a low-cost, safe and environmentally friendly food preservation effect.

CN119591912APending Publication Date: 2025-03-11SHANGHAI INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411633212.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing bacterial cellulose application in food packaging materials is costly, complicated to operate, may involve harmful reagents and waste.

Method used

By combining bacterial cellulose with natural materials such as chitosan and cinnamon essential oil, antibacterial and antioxidant composite materials are prepared by emulsion coating and non-covalent bonding technology, and bacterial cellulose active composite materials are prepared by casting into films.

Benefits of technology

It achieves low-cost, simple process, safe and environmentally friendly food preservation effect, significantly maintains the quality of fresh food, and has high internal safety and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591912A_ABST
    Figure CN119591912A_ABST
Patent Text Reader

Abstract

The invention relates to a bacterial cellulose active composite material and a preparation method and application thereof, and the preparation method comprises the following steps: crushing bacterial cellulose to prepare bacterial cellulose homogenate, then adding active components for homogenization to obtain an active component-bacterial cellulose emulsion, adding a film-forming agent and a plasticizer into the emulsion, and uniformly stirring to obtain the bacterial cellulose active composite material. And pouring the mixed solution into a mold, drying, and demolding to obtain the product. In a preferable scheme of the invention, the active component is cinnamon essential oil, the film-forming agent is chitosan, and the plasticizer is glycerol. The bacterial cellulose active composite material prepared by the invention is safe, green and degradable, has good oxidation resistance and broad-spectrum antibacterial activity, can delay browning and decay of fresh fruits and vegetables so as to prolong the shelf life of the fruits and vegetables, also provides a new method for recycling bacterial cellulose and residual materials thereof, and has wide application prospects. The application of the bacterial cellulose in the field of food preservation is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fruit and vegetable preservation, and in particular to a bacterial cellulose active composite material and a preparation method and application thereof. Background Art

[0002] Bacterial cellulose (BC) is a class of high molecular compounds produced by bacteria such as Acetobacter xylinum during metabolism and is an emerging environmentally friendly material. It is a linear macromolecular polysaccharide chain polymerized from β-D-glucose, which has the same structure and similar chemical composition as plant-derived cellulose. However, due to the strong intramolecular and intermolecular hydrogen bonding in the crystalline region, bacterial cellulose has the characteristics of high polymerization degree and high crystallinity, and is difficult to dissolve and regenerate into a film. Compared with plant cellulose, BC has higher purity and has some excellent properties such as high elastic modulus and tensile strength. Under natural conditions, BC can be degraded by microorganisms into small molecular glucose, which has strong biocompatibility and degradability. More importantly, BC was recognized as a safe food additive by the U.S. Food and Drug Administration (FDA) as early as 1992. It has many important physiological functions, such as reducing the risk of chronic diseases such as diabetes, obesity, cardiovascular disease and diverticulitis. It is an excellent food raw material and has been widely used in the food field.

[0003] For example, patent CN115636961A provides an antibacterial and antioxidant gelatin-based composite film and its preparation method, wherein the gelatin-based antibacterial and fresh-keeping composite film is prepared by a casting method using a 1.0wt% TOBC-stabilized Pickering emulsion and gelatin as building units; the gelatin-based antibacterial and fresh-keeping composite film has excellent antibacterial activity, antioxidant capacity, water resistance and water insolubility. However, the film-forming matrix in the patent needs to be dissolved at a higher temperature, and the preparation process of the TEMPO-oxidized bacterial cellulose used in the patent may be complicated and costly, thereby increasing the overall cost of the composite film.

[0004] Patent CN114369292B discloses a carboxymethyl chitosan / bacterial cellulose / nano-silicon dioxide active packaging film, wherein the active packaging film is a composite film prepared from carboxymethyl chitosan, bacterial cellulose, nano-silicon dioxide, a cross-linking agent and a plasticizer, wherein the mass ratio of carboxymethyl chitosan, bacterial cellulose, nano-silicon dioxide and a plasticizer is 1-2:3-6:0.5-1:0.2-0.5, and the content of the cross-linking agent is 5wt% to 10wt% of the carboxymethyl chitosan. The carboxymethyl chitosan / bacterial cellulose / nano-silicon dioxide active packaging film of the invention has good antibacterial properties, antioxidant properties and mechanical properties, and has high toughness, strong barrier properties, cost saving and safety and environmental protection. However, some chemical reagents (such as glutaraldehyde) used in the preparation process of the composite film in the patent may have certain pollution risks and safety issues.

[0005] Patent CN113927965A discloses a photosensitive antibacterial and antioxidant composite cling film based on nano bacterial cellulose, which includes a photodynamic antibacterial film, a nano bacterial cellulose-based antioxidant and anti-browning film, and a nano bacterial cellulose-based antibacterial base film from top to bottom; the composite cling film of the present invention has good film-forming properties and mechanical properties, as well as a low water vapor permeability coefficient and good antibacterial activity, which can avoid a large amount of water loss in food and achieve a good preservation effect. The preparation of the composite cling film in this patent involves multiple steps, such as multi-step pre-dispersion, electrostatic spinning, electrostatic self-assembly, etc., which is complicated to operate and has high requirements for equipment and technicians.

[0006] In summary, the existing bacterial cellulose has the disadvantages of high cost, complicated operation and possible involvement of harmful reagents in the steps when applied to food outer packaging materials; in addition, most BC can only be applied in the form of films, and a large amount of bacterial cellulose residues produced during the initial production can only be discarded because they cannot be made into downstream products, resulting in a huge waste of this biomaterial, which limits its application in the field of food preservation. Summary of the invention

[0007] In view of the above defects, the purpose of the present invention is to provide a bacterial cellulose active composite material and its preparation method and application. This application combines bacterial cellulose BC with other natural materials such as film-forming agents, active ingredients with antibacterial and antioxidant functions, etc. to prepare packaging materials, which is an important means to expand the application scope of bacterial cellulose in food preservation.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] One of the technical solutions of the present invention is to provide a method for preparing a bacterial cellulose active composite material, comprising the following steps:

[0010] S1. crushing the bacterial cellulose to prepare a bacterial cellulose homogenate; adding the active ingredient to the homogenate and homogenizing to obtain an emulsion;

[0011] S2. The film-forming agent is dissolved in an acetic acid solution, and a plasticizer is added; and the emulsion obtained in step S1 is mixed uniformly to obtain a mixed solution;

[0012] S3. The mixed solution obtained in step S2 is cast into a mold by a casting film method, and the bacterial cellulose active composite material is obtained by drying and demolding.

[0013] Furthermore, in step S1, the mass concentration of the bacterial cellulose homogenate is 1-5%.

[0014] Further, in step S1, the active ingredient is selected from at least one of cinnamon essential oil, oregano essential oil, and clove essential oil. Preferably, the active ingredient is cinnamon essential oil.

[0015] Furthermore, in step S1, the ratio of the active ingredient to the bacterial cellulose homogenate is (0.8-1.2) mL:4 mL.

[0016] Furthermore, in step S1, the homogenization speed is 5000-15000 rpm, and the time is 2-10 min.

[0017] In some embodiments, the bacterial cellulose is obtained by using Acetobacter xylinum ATCC 23770 as the strain, and is cultured statically or dynamically in a liquid culture medium at a constant temperature of 28-32° C. for 3-7 days, then placed in a 1%-5% (w / v) sodium hydroxide solution, treated at 70-90° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral.

[0018] Further, in step S2, the film-forming agent is selected from any one of chitosan and polyvinyl alcohol;

[0019] Furthermore, in step S2, the concentration of the acetic acid solution is 0.8-1.2%.

[0020] Furthermore, in step S2, the mass volume ratio of the film-forming agent to the acetic acid solution is 1 g:(25-95) mL; preferably 1 g:95 mL.

[0021] Furthermore, in step S2, the amount of the plasticizer added is 10-40% based on the dry weight of the film-forming agent; the plasticizer is selected from at least one of glycerol sorbitol, polyethylene glycol, and stearic acid. Preferably, the plasticizer is glycerol. In some embodiments, the plasticizer is glycerol, and the amount added is 40% (the film-forming agent is chitosan).

[0022] In some preferred embodiments of the present application, the film former is chitosan, and the active ingredient is cinnamon essential oil. Chitosan, cinnamon essential oil and bacterial cellulose are mainly connected by non-covalent bonding technology, and the non-covalent bonding technology refers to the technology of connecting molecules or materials together by non-covalent bond interactions. Non-covalent bonding refers to the combination of molecules or atoms within molecules through weaker interactions, which are not formed by sharing electron pairs, and mainly include hydrogen bonds, van der Waals forces, π-π stacking, etc. Van der Waals forces are widely present between various molecules. In addition, a large number of studies have shown that there are strong hydrogen bonds between bacterial cellulose, chitosan and cinnamon essential oil.

[0023] Furthermore, in step S3, the drying treatment is carried out at a temperature of 40°C-100°C and for a time of 1-24 hours.

[0024] In some embodiments, in step S3, the mold used for drying is preferably a plastic dish of 25 cm×25 cm.

[0025] The second technical solution of the present invention is to provide a bacterial cellulose active composite material, which is prepared based on the preparation method described in one of the above technical solutions.

[0026] The third technical solution of the present invention is to provide an application of a bacterial cellulose active composite material, wherein the bacterial cellulose active composite material is used as food outer packaging for preserving fruits and vegetables.

[0027] In some specific embodiments, the bacterial cellulose active composite material is used to preserve fresh walnut kernels.

[0028] The beneficial effects of the present invention are:

[0029] (1) The raw material bacterial cellulose used in the present invention is prepared by microbial fermentation and is also a natural dietary fiber, which has the advantages of being non-toxic, highly safe, biodegradable and renewable.

[0030] (2) The present invention prepares a composite material with antibacterial and antioxidant properties through emulsion coating and non-covalent bonding technology, and can be prepared into any size and shape based on a mold. The prepared composite material has high in vivo safety and can be completely degraded in nature, and is an environmentally friendly material.

[0031] (3) The active composite material prepared by the present invention has good antibacterial and antioxidant properties, and its functionality is also better than the cling film currently on the market. It can significantly maintain the quality of fresh food (such as fresh walnut kernels), including acid value, peroxide value, total colony count, etc.

[0032] (4) The method of the present invention has simple process, low cost, easy to put into industrial production, high efficiency and less pollution to the environment, and can become a way to efficiently utilize biomass raw materials to prepare new functional materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The preparation process of the composite membrane of the present invention is as follows;

[0034] Figure 2 The results of the inhibition zone test of chitosan (CS), chitosan-bacterial cellulose (CS-BC), and chitosan-bacterial cellulose-cinnamon essential oil (CS-BC-CEO) composite films on Escherichia coli and Staphylococcus aureus are shown in Figure 1 (a in the figure indicates the results of the inhibition zone test of Escherichia coli; b indicates the results of the inhibition zone test of Staphylococcus aureus);

[0035] Figure 3 The growth curve test results of CS, CS-BC, and CS-BC-CEO on Escherichia coli and Staphylococcus aureus (a in the figure represents: the growth curve test result of Escherichia coli; b represents: the growth curve test result of Staphylococcus aureus);

[0036] Figure 4 is the inhibition rate of CS, CS-BC, and CS-BC-CEO against Escherichia coli and Staphylococcus aureus;

[0037] Figure 5 The DPPH and ABTS free radical scavenging rate test results of CS, CS-BC, and CS-BC-CEO are shown in the figure (a in the figure indicates: DPPH free radical scavenging rate test results; b indicates: ABTS free radical scavenging rate test results);

[0038] Figure 6 To study the changes in moisture content during storage of fresh walnuts using CS-BC composite film, CS-BC-CEO composite film, blank (no treatment) and PE (treated with commercially available PE film);

[0039] Figure 7 To study the changes of peroxide value during the storage of fresh walnuts using CS-BC composite film, CS-BC-CEO composite film, blank (no treatment) and PE (treated with commercially available PE film);

[0040] Figure 8 To study the changes of total phenolic content in fresh walnuts during storage using CS-BC composite membrane, CS-BC-CEO composite membrane, blank (no treatment) and PE (treated with commercially available PE membrane);

[0041] Fig. 9To study the changes of polyphenol oxidase activity during the storage of fresh walnuts using CS-BC composite film, CS-BC-CEO composite film, blank (no treatment) and PE (treated with commercially available PE film). DETAILED DESCRIPTION

[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0043] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0044] Acetobacter xylinum: ATCC 23770, American Type Culture Collection.

[0045] Example 1

[0046] Preparation of bacterial cellulose (BC)

[0047] (1) The bacterial cellulose film is prepared by fermenting Acetobacter xylinum (ATCC 23770, from the American Type Culture Collection) in a fixed fermentation culture. Acetobacter xylinum is used as the strain and is cultured statically or dynamically at 30° C. for 7 days in a liquid culture medium containing 3 g / L tryptophan, 25 g / L glucose and 5 g / L yeast extract. The pH value of the liquid culture medium is adjusted to 5.0 with 80% (v / v) sulfuric acid. After the bacterial cellulose film is formed, it is taken out for use.

[0048] (2) The BC membrane was repeatedly washed with distilled water to remove residual culture medium components. The membrane was purified by placing it in a 1% (w / v) sodium hydroxide solution at 95°C for 4 h to remove residual bacteria and other organisms.

[0049] (3) The BC membrane was repeatedly washed with deionized water until the pH value of the washing solution was neutral. The washed BC membrane was sterilized at 121°C for 20 min and stored at 4°C until further use.

[0050] Example 2

[0051] Preparation of chitosan / bacterial cellulose / cinnamon essential oil membrane (CS-BC-CEO)

[0052] (1) The BC membrane obtained in Example 1 was crushed, deionized water was added, and homogenized with a high-speed homogenizer at 10,000 rpm for 30 min to prepare a homogenate with a mass concentration of 1%.

[0053] (2) Preparation of cinnamon essential oil-bacterial cellulose emulsion:

[0054] 2 mL of cinnamon essential oil (CEO) was added to 8 mL of bacterial cellulose (BC, 1 wt%) slurry prepared in step (1), and homogenized at 15000 rpm for 2 min to obtain cinnamon essential oil-bacterial cellulose Pickering emulsion (CEO-BC-PEs).

[0055] (3) Weigh 2 g of chitosan powder and dissolve it in 190 mL of acetic acid (1 v / v%), stir it magnetically at room temperature for 2 h, then add 40% (based on the dry weight of chitosan) of glycerol as a plasticizer, and then add 10 mL of the cinnamon essential oil-bacterial cellulose Pickering emulsion (CEO-BC-PEs) prepared in step (2) to mix and obtain a composite membrane liquid. Pour the prepared composite membrane liquid into a plastic mold of 25 cm × 25 cm in size by solution casting, dry it at 25°C for 48 h, and peel off the film after film formation. The prepared composite membrane is named CS-BC-CEO.

[0056] The composite membrane was equilibrated at 25°C and 53% relative humidity for 48 h before use.

[0057] Comparative Example 1

[0058] Preparation of chitosan film (CS)

[0059] Weigh 2 g of chitosan powder and dissolve it in 190 mL of acetic acid (1 v / v%), stir it magnetically at room temperature for 2 h, then add 40% (based on the dry weight of chitosan) of glycerol as a plasticizer, and pour the prepared membrane liquid into a plastic mold of 25 cm × 25 cm by solution casting. Dry it at 25 ° C for 48 h, and peel off the film after it is formed. The prepared composite membrane is named CS.

[0060] The composite membrane was equilibrated at 25°C and 53% relative humidity for 48 h before use.

[0061] Comparative Example 2

[0062] Preparation of chitosan / bacterial cellulose membrane (CS-BC)

[0063] (1) The BC membrane obtained in Example 1 was crushed, deionized water was added, and homogenized with a high-speed homogenizer at 10,000 rpm for 30 min to prepare a homogenate with a mass concentration of 1%.

[0064] (2) Weigh 2 g of chitosan powder and dissolve it in 190 mL of acetic acid (1 v / v%), stir it magnetically at room temperature for 2 h, then add 40% (based on the dry weight of chitosan) of glycerol as a plasticizer, and then add 10 mL of the BC slurry prepared in step (1), and homogenize it at 15,000 rpm for 2 min. Pour the prepared membrane liquid into a plastic mold of 25 cm × 25 cm by solution casting, dry it at 25°C for 48 h, and peel off the membrane after it is formed. The prepared composite membrane is named CS-BC.

[0065] The composite membrane was equilibrated at 25°C and 53% relative humidity for 48 h before use.

[0066] Example 3

[0067] Determination of antibacterial activity of composite films

[0068] The antibacterial experiments were carried out using Escherichia coli and Staphylococcus aureus. The antibacterial properties of CS, CS-BC and CS-BC-CEO were determined by inhibition zone test and growth curve test.

[0069] For the inhibition zone test, the composite film was first cut into discs with a diameter of 16 mm and irradiated with ultraviolet light for 30 min. The agar medium was poured into a culture dish and, after solidification, 100 μL of bacterial culture solution (1-3×10 5 cfu / mL) was evenly spread on the plate. The sterile composite film was placed on the surface of the culture dish with tweezers, cultured at 37°C for 24 hours, and its antibacterial activity was evaluated by measuring the size of the inhibition zone. The culture medium used for Escherichia coli and Staphylococcus aureus was LB culture medium.

[0070] For the growth curve test, 10 mL of membrane solution was added to 100 mL of liquid culture medium, and then 1 mL of bacterial culture medium was inoculated and cultured in a shaker at 37°C and 160 rpm. The absorbance at 600 nm was measured every 2 hours, and each test was repeated 3 times. The calculation formula for the inhibition rate is as follows:

[0071] Inhibition rate = (Abs 空白 -Abs 试验 ) / Abs 空白 ×100%

[0072] Among them, Abs 空白 and Abs 试验 They are the absorbance of blank group and different sample test groups at 600nm.

[0073] Figure 2a and b are the results of the inhibition zone test of CS, CS-BC, and CS-BC-CEO on Escherichia coli and Staphylococcus aureus, respectively. As can be seen from the figure, CS-BC-CEO has a good antibacterial effect on Staphylococcus aureus and Escherichia coli, which may be related to the active compounds in CEO. Due to its hydrophobicity, CEO can easily penetrate into the phospholipid bilayer of bacteria, destroy the cell wall, and cause leakage of cell contents. CEO can also inhibit cell respiration by affecting related enzymes that cause cell death. The sizes of the inhibition zones of CS and CS-BC are similar, both smaller than the inhibition zone of CS-BC-CEO. This may be because CS has certain antibacterial properties, while BC has no antibacterial properties, and the antibacterial properties of the two membranes mainly come from CS. The antibacterial activity of CS comes from the interaction of its positively charged amino groups with negatively charged molecules on the cell surface, affecting the permeability of the cell membrane.

[0074] Figure 3 a and b are the growth curves of Escherichia coli and Staphylococcus aureus, respectively. Figure 4 The inhibition rates of CS, CS-BC, and CS-BC-CEO against Escherichia coli and Staphylococcus aureus. The growth rate of bacteria in the blank control group was the fastest because no sample was added. The growth rate of bacteria was significantly inhibited after adding CS and CS-BC, indicating that both CS and CS-BC have certain antibacterial properties. The bacteria in the CS-BC-CEO group grew the slowest, which is due to the strong antibacterial property of CEO. The inhibition rates of different samples are shown in Figure 2. Figure 4 As shown, the inhibition rates of different samples against Staphylococcus aureus were higher than those against Escherichia coli, among which the inhibition rates of CS-BC-CEO against Escherichia coli and Staphylococcus aureus were 50% and 65%, respectively. This may be due to the intrinsic differences in the cell wall structure between the two bacteria. Gram-negative bacteria have an outer membrane on their cell walls, making it more difficult for antibacterial components to enter the cells.

[0075] Example 4

[0076] Determination of oxidation resistance of composite films

[0077] The antioxidant activity of the composite membranes was determined by DPPH and ABTS methods.

[0078] For the DPPH test, samples with different membrane equivalents (0.5-8 mg / mL) were mixed with 1 mL of DPPH ethanol solution (0.1 mmol / L). After 2 h of dark reaction, the absorbance was measured at a wavelength of 517 nm.

[0079] The working solution of the ABTS experiment is 7mM ABTS stock solution and 2.45mM potassium persulfate, which reacts in the dark at room temperature for 12-16h. The solution is then diluted with deionized water to obtain an absorbance of 0.70±0.02 at 734nm. Different film equivalent samples (0.5-8mg / mL) are mixed with 1ml ABTS solution in the dark for 30min, and then the absorbance of the mixture is measured at a wavelength of 734nm. The free radical scavenging rate (RSA) is calculated as follows:

[0080] RSA(%)=(A 空白 -A 样品 ) / A 空白 ×100

[0081] Among them, A 空白 is the absorbance of the blank group, A 样品 is the absorbance of the test group.

[0082] The results are as follows Figure 5 As shown in a and b, the antioxidant capacity of all samples was dose-dependent. The antioxidant activity of CS and CS-BC mainly comes from the amino group at the C2 position in CS. The scavenging rates of CS and CS-BC (8 mg / mL membrane equivalent) for ABTS and DPPH free radicals were about 50% and 35%, respectively. The addition of CEO-BC-PEs significantly improved the antioxidant activity of the membrane, and the scavenging rates of CS-BC-CEO (8 mg / mL membrane equivalent) for DPPH and ABTS free radicals were 60% and 55%, respectively. This is due to the strong antioxidant activity of CEO, which contains a variety of terpenes and phenolic acids, which have good free radical scavenging ability.

[0083] Example 5

[0084] Application of composite film in storage of fresh walnut kernels

[0085] In this example, CS-BC-CEO, CS-BC, and PE (commercially available PE film) were selected as the experimental group, and a blank group without any treatment was used as the control to study the application of the composite film in the storage of fresh walnut kernels.

[0086] Figure 6-9 This study investigates the changes in moisture content, peroxide value (PV), total phenol content and polyphenol oxidase activity (PPO) of fresh walnut kernels during storage.

[0087] For moisture content, refer to the weighing method in GB / T5497-1985, weigh 2g of fresh kernel sample, record its weight as M1, and then place it in a constant temperature forced air drying oven for drying (the temperature is adjusted to 105±2℃), take it out and weigh it every 30 minutes, and dry it until the difference between the two weights does not exceed 0.005g, record it as M2, and (M1-M2) / M1 is the moisture content of the kernel.

[0088] For the peroxide value (PV), refer to the titration method in GB / T5009.227-2016, use the Soxhlet extraction method to extract walnut oil, weigh 0.5g walnut oil, add 30mL chloroform-glacial acetic acid mixture (chloroform and glacial acetic acid volume ratio 40:60), shake gently to dissolve the sample completely, add 1mL saturated potassium iodide solution, shake gently for 30s, and place in the dark for 3min. Take out the mixed solution and add 100mL distilled water. After shaking well, immediately titrate with 0.002mol / L sodium thiosulfate standard solution. When titrated to light yellow, add 1mL starch indicator, continue titration and shake vigorously until the blue color of the solution disappears as the end point. The volume of sodium thiosulfate solution consumed is recorded as V. At the same time, a blank test is performed, and the volume of sodium thiosulfate solution consumed in the blank test is recorded as V0. The peroxide value is expressed as the number of millimoles of active oxygen in 1kg sample, and is calculated according to the following formula:

[0089]

[0090] Where:

[0091] X represents the peroxide value, in millimole per kilogram (mmol / kg); V represents the volume of sodium thiosulfate standard solution consumed by the sample, in milliliter (mL); V0 represents the volume of sodium thiosulfate standard solution consumed by the blank test, in milliliter (mL); c represents the concentration of the sodium thiosulfate standard solution, in mole per liter (mol / L); m represents the mass of the sample, in gram (g); and 1000 represents the conversion factor.

[0092] For total phenol content, first weigh 10 mg (accurate to 0.1 mg) of gallic acid standard, dissolve and dilute to 100 mL to obtain a 0.1 mg / mL standard solution; measure 0.0 mL, 0.25 mL, 0.50 mL, 0.75 mL, 1.00 mL, 1.25 mL, and 1.5 mL of gallic acid standard solution and dilute to 25 mL. Accurately measure 1.0 mL of gallic acid standard series concentration solution in a 25 mL test tube, add 1 mL of Folin-Phenol reagent (1 mol / L), shake well and let stand for 5 min, then add 2 ml of Na2CO3 solution 12% (w / v), add water to the scale line, heat in a 30°C water bath for 90 min, and measure the absorbance at 765 nm. Draw a standard curve with gallic acid concentration (μg / mL) as the horizontal axis and absorbance as the vertical axis. Weigh 0.5g of the nucleolus sample accurately, grind it thoroughly with 70% ethanol in a pre-cooled mortar and then dilute to 10mL, then extract in a 60℃ water bath for 30min, centrifuge at 8000r / min and 4℃ for 10min, and take the supernatant as the sample solution. When measuring, take 1mL of the sample solution, add 1mL of Folin-Phenol reagent (1mol / L), then add 2ml of Na2CO3 solution 12% (w / v), add water to dilute to the scale line and mix well, after 10min in a 70℃ water bath, measure the absorbance at a wavelength of 765nm. The total phenol content is expressed in mg / g FW.

[0093] For polyphenol oxidase activity (PPO), weigh 1g of nucleolus, add 8mL of 0.1mol / L sodium phosphate buffer (pH6.8) (containing 1% (v / v) tritonX-100 and 4 (w / w)% pvp) and homogenize in an ice bath, centrifuge at 10000g for 20min. Take 0.5mL of supernatant, add 2mL of sodium phosphate buffer (0.1mol / L, pH6.8) and 2mL of catechol solution (50mmol / L) and mix well. After adding 0.2mL of H2O2 solution (2%), immediately measure the change of absorbance at 470nm within 5min. Enzyme activity is calculated as Ug -1 FW, a change in absorbance of 0.1 within 1 min was defined as one enzyme activity unit (U).

[0094] One of the main reasons why fruits and vegetables lose weight during storage is evaporation of water. Figure 6 The results show the changes in moisture content of fresh walnut kernels during storage. Compared with the blank group, both CS-BC and CS-BC-CEO can effectively reduce the loss of moisture. The weight loss rate of fresh walnut kernels in the PE group was the smallest during the entire storage period, which is due to the strong moisture retention of the PE film. The results show that the CS-based film can effectively prevent the loss of moisture in fresh walnut kernels during storage at 4°C.

[0095] Peroxide value is an important indicator for judging the degree of oil rancidity. Figure 7 As shown in the figure, the PV values ​​of all samples increased with the increase of storage time. During the entire storage period, there was no significant difference in the PV values ​​between PE, CS-BC and the control group, while the CS-BC-CEO treatment significantly delayed the increase in the PV value, indicating that the CS-BC-CEO composite film can effectively delay the oxidation of oil. This is because the CEO in CS-BC-CEO is slowly released to the surface of walnuts, providing hydrogen atoms for lipid free radicals or peroxyl free radicals and removing them, thereby blocking the chain reaction of free radicals and hindering the occurrence of oxidation reactions.

[0096] Total phenols are an important class of bioactive components in walnut kernels and have antioxidant activity. Figure 8 As shown, at the end of storage, the total phenolic content in the CS-BC-CEO group was the highest, which may be related to the interaction and activity changes of some enzymes that oxidize phenolic substances.

[0097] Polyphenol oxidase (PPO) can catalyze and accelerate the degradation of phenol, causing browning of fruits and vegetables. Fig. 9 As shown in the results, compared with the blank group, the PE film showed almost no effect of inhibiting PPO activity in the first 9 days, while the CS-BC treatment significantly inhibited the increase of PPO activity, and CS-BC-CEO further enhanced this effect. This shows that CS-BC-CEO can effectively inhibit PPO activity. The inhibitory effect of CS-BC-CEO treatment on PPO activity may be related to maintaining good cell membrane integrity, mild oxidative damage, forming a protective barrier on the fruit surface, and reducing oxygen supply.

[0098] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a bacterial cellulose active composite material, characterized in that: The steps include: S1. crushing the bacterial cellulose to prepare a bacterial cellulose homogenate; adding the active ingredient to the bacterial cellulose homogenate and homogenizing to obtain an emulsion; S2. The film-forming agent is dissolved in an acetic acid solution, and a plasticizer is added; and the emulsion obtained in step S1 is mixed uniformly to obtain a mixed solution; S3. The mixed solution obtained in step S2 is cast into a mold by a casting film method, and the bacterial cellulose active composite material is obtained by drying and demolding.

2. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: In step S1, the mass concentration of the bacterial cellulose homogenate is 1-5%.

3. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: In step S1, the active ingredient is selected from at least one of cinnamon essential oil, oregano essential oil, and clove essential oil; and the ratio of the active ingredient to bacterial cellulose homogenate is (0.8-1.2) mL:4 mL.

4. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: In step S1, the homogenization speed is 5000-15000 rpm, and the time is 2-10 min.

5. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: In step S2, the film-forming agent is selected from any one of chitosan and polyvinyl alcohol; the concentration of the acetic acid solution is 0.8-1.2%; the mass volume ratio of the film-forming agent to the acetic acid solution is 1g:(25-95)mL.

6. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: In step S2, the amount of the plasticizer added is 10-40% based on the dry weight of the film-forming agent; the plasticizer is selected from any one of glycerol, sorbitol, polyethylene glycol, and stearic acid.

7. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: In step S3, the drying process is carried out at a temperature of 40°C-100°C and for a time of 1-24 hours.

8. The method for preparing a bacterial cellulose active composite material according to claim 1, characterized in that: The active ingredient is cinnamon essential oil, the film-forming agent is chitosan, and the plasticizer is glycerol.

9. A bacterial cellulose active composite material, characterized in that: The composition is prepared by the method for preparing a bacterial cellulose active composite material according to any one of claims 1 to 8.

10. The use of a bacterial cellulose active composite material according to claim 9, characterized in that: The bacterial cellulose active composite material is used for making food outer packaging.

Citation Information

Patent Citations

  • Photosensitive antibacterial antioxidant composite preservative film based on nanometer bacterial cellulose as well as preparation method and application of photosensitive antibacterial and antioxidant composite preservative film

    CN113927965A